Potassium Tantalate K6Ta10.8O30 with Tungsten Bronze Structure and Its Photocatalytic Property. Issue 2 (13th February 2017) - Wang, Junting; Xiao, Chun; Wu, Xiaoyong; Zhang, Gaoke
Abstract : With the tunable and flexible physicochemical properties, tantalate photocatalysts with tungsten bronze structure are worth being studied. In this work, we successfully synthesized a novel potassium tantalate K6 Ta10.8 O30 with tungsten bronze structure using a facile solid‐state reaction route. The effects of calcination time on the phase composition, morphology and crystallinity of the obtained samples were studied by XRD and SEM analyses. In addition, the photocatalytic activity of the samples was evaluated by the degradation of ARG dye under UV light irradiation. The results indicated that the K6 Ta10.8 O30 showed high photocatalytic activity for degradation of ARG and the photocatalytic degradation of ARG followed the first order kinetics. Furthermore, the possible photocatalytic mechanism of the K6 Ta10.8 O30 photocatalyst was proposed based on tungsten bronze structure feature and the scavengers experimental results. This study would give a new insight into tantalate photocatalysts. Abstract : A novel potassium tantalate K6 Ta10.8 O30 with tungsten bronze structure was prepared by a facile solid‐phase method, which shows high photocatalytic activity of the degradation of ARG dye under UV irradiation.